Synthesis and characterization of FeTiO3 ceramics - Gambhire, Anil B.; Lande, Machhindra K.; Rathod, Sandip B.; Arbad, Balasaheb R.; Vidhate, Kaluram N.; Gholap, Ramakrishna S.; Patil, Kashinath R. (Arabian Journal of Chemistry, 2016)
Nanocrystalline FeTiO3 ceramics powders were prepared by the sol-gel process combined with a surfactant-assisted template method. The resulting powders were calcined at different temperatures ranging from 150 degrees C to 600 degrees C for 2 h in an air. The results revealed that a pure hexagonal phase of FeTiO3 could be obtained at low temperature, 600 degrees C. The phase evolution of FeTiO3 was investigated by X-ray diffraction patterns (XRD), Fourier-transform infrared spectroscopy (FT-IR), and X-ray photoelectron spectroscopy (XPS). Particle size and morphology was studied by transmission electron microscopy (TEM). (C) 2011 Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Electron microscopy; hexagonal phase; Nanoparticles; sol-gel process; Ti-O bond